Abrikosov flux lattice in planar crystals of YBa2Cu3O7- delta. - Barford, W; Harrison, M (1994)
Anisotropic London theory is used to predict the Abrikosov flux lattice for arbitrary field orientations in crystals of YBa2Cu3O7- by minimizing the Gibbs free energy for samples of a planar geometry. At low fields the vortex-chain state exists, i.e., the interchain vortex separation scales as the inverse flux density 1/B whereas the intrachain vortex seperation is constant. At higher fields there is a crossover to the uniaxially distorted hexagonal lattice where the intervortex separation scales as 1/B1/2. At low fields the vortex lattice is inclined towards the c^ axis, rotating towards the applied field at higher fields. The results of this calculation are in close agreement to the Bitter pattern experiments of Gammel et al. [Phys. Rev. Lett. 68, 3343 (1992)] assuming an anisotropy ratio of 5 and an in-plane penetration depth a of 1 413, indicating that the vortex-chain state has been observed in these experiments. © 1994 The American Physical Society.